Application of Learning Cycle 7e on Environmental Pollution Material Toward Students' Interest and Learning Outcomes in Class X - Fauzy, Rahmad; Nirmalasari, Ridha; Rohmadi , Mukhlis (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
This study aims to describe the learning interest and cognitive learning outcomes of students with the Learning Cycle 7E learning model on environmental pollution material. This research uses a quantitative approach with the type of Pre-Experimental Design and One Group Pretest-Posttest design. The research sample was all students of class X SMA Negeri 1 Antang Kalang. The research instruments included learning interest questionnaire, cognitive learning outcomes test, and learning applicability observation sheet. Questionnaires and tests were given before and after the implementation of the Learning Cycle 7E model, while observations were made during the learning process. Data analysis shows that interest in learning based on the calculation of N-gain testing using excel shows there is an increase but still low. While the cognitive learning outcomes between pretest and postest experienced changes but classically said to be incomplete. This model also shows a high level of applicability, indicating its suitability for the context of biology learning at the high school level.